The efficacy of epidural ropivacaine 0.75% and levobupivacaine 0.5% in abdominal and lower limb surgeries- a comparative study - S., Kiran Kumar; Rao, Kishan (International Journal of Research in Medical Sciences, 2016)
Background: Both levobupivacaine and ropivacaine are relatively new long acting amide local anaesthetics. Both are pure S-enantiomers of the parent drug racemic bupivacaine. Little is known about the comparative efficacy of epidural levobupivacaine with this another widely used long-acting local anaesthetic, ropivacaine. Methods: We compared the efficacy of levobupivacaine 0.5% with ropivacaine 0.75% in epidural route in a volume of 20ml in 100 adult patients who were divided into two groups of 50 patients each, belonging to ASA grade 1and 2, of either gender, between the age group of 18-60 years undergoing lower abdominal surgeries. Results: Our study has not shown statistically significant difference between the drugs in sensory block characteristics such as mean onset time of sensory blockade, mean time to attain maximum sensory level, maximum level of sensory blockade, two segment regression time, and duration of analgesia. Also motor parameters such as mean time of onset of motor block, and duration of motor block and quality of motor block were comparable between the groups with a statistically insignificant p value. With respect to, haemodynamic parameters and side effect profiles, both Levobupivacaine and Ropivacaine were comparable. Conclusions: The present study concludes that 0.5% levobupivacaine and 0.75% ropivacaine were clinically similar with respect to sensory block characteristics and duration of analgesia, quality of motor blockade with minimal side effects in both the groups. Both drugs could be better alternatives to bupivacaine in epidural anaesthesia.